Prevalence and characterization of ESBL-producing Escherichia coli in healthy pregnant women and hospital environments in Benin: an approach based on Tricycle - Sintondji, Kevin; Fabiyi, Kafayath; Hougbenou, Jules; Koudokpon, Hornel; Lègba, Boris; Amoussou, Hornella; Haukka, Kaisa; Dougnon, Victorien (Frontiers in Public Health, 2023)
Extended-spectrum β-lactamase (ESBL)-producing Enterobacterales are recognized as significant pathogens due to their resistance to multiple antibiotics. This study aimed to determine the prevalence of ESBL-producing Escherichia coli (E. coli) in healthy pregnant women, the food chain, and the environment of various tertiary hospitals in Benin. Samples were collected from healthy pregnant women (feces), foods sold in hospital canteens, and hospital effluents across four hospitals in southern Benin. Fecal samples were plated on MacConkey agar supplemented with cefotaxime (4µg/ml), while food and water samples were plated on Tryptone Bile X agar and Tryptone Bile X agar supplemented with cefotaxime (4μg/ml). Representative E. coli colonies were purified and identified using urea indole tests, followed by confirmation of ESBL production using the double disk synergy technique. The antibiotic susceptibility of ESBL-producing E. coli strains was determined using the disk diffusion method on MH agar. PCR was employed to investigate the presence of ESBL encoding genes. Among the 296 fecal samples collected from four tertiary hospitals, ESBL-producing E. coli was isolated from 22.30% (66) of the samples. All E. coli isolates from hospital effluents exhibited ESBL production, while ESBL-producing E. coli was not detected in food and drinking water samples. The analysis of variable associations showed no significant associations (p>0.05) for the studied factors. Antibiotic susceptibility testing revealed high resistance rates among ESBL-EC isolates against several tested antibiotics, including amoxicillin, aztreonam, ceftriaxone, ciprofloxacin, and trimethoprimsulfamethoxazole. However, most isolates remained susceptible to ertapenem, amoxicillin-clavulanate, and imipenem. The most prevalent ESBL encoding genes were blaTEM (37.5%), blaOXA-1 (19.44%), and blaSHV (11.11%), while a smaller proportion of isolates carried blaCTXM-1/blaCTXM-15 (5.55%) and blaCTXM-9. This study provides insights into the prevalence of ESBL-producing E. coli carriage in the feces of healthy pregnant women in southern Benin and highlights hospital wastewater as a potential reservoir of ESBL-producing bacteria in the environment.